The Effect of Playing Cards with Mosquito Claps on Cognitive Function and Happiness in Elderly Residents - Rahmah, Aldila Dwi Nur; Isnaini, Nur Isnaini (Sarana Ilmu Indonesia (salnesia), 2024)
The study aimed to investigate the impact of playing playing cards with mosquito claps on cognitive function and happiness levels in the elderly living in the Sudagaran Banyumas Elderly Social Service Center. This research used a method of Quasy Experimental Non-Equivalent Control Group Design with pretest-posttest with quantitative data analysis. The research was conducted at the Sudagaran Elderly Social Service Home, as many as 32 subjekts with purposive sampling technique. The analysis used is Wilcoxon test, Mann-Whitney test and Effect Size. Based on the results of the Mann-Whitney test from the posttest results of cognitive function and happiness of the intervention group and control group, the p-value of cognitive function was 0,005 (p<0,05) and the p-value of happiness was 0,001 (p<0,05), meant that there was a significant effect on cognitive function and happiness of the elderly in the intervention group and control group with an effect size of 0,698 on cognitive function and 0,826 on happiness. The result of this study was that there was a difference between before and after playing cards with mosquito claps on the intervention group and control group and a large effect on cognitive function with an effect size of 0,698 and happiness with an effect size of 0,826. Playing cards is a useful activity for the elderly in improving cognitive function and increasing their happiness. This can help them feel more comfortable and enjoy old times more pleasantly.